Wages, experience and training of women over the lifecycle - Richard W. Blundell; Monica Costa Dias; David Goll; Costas Meghir (Institute for Fiscal Studies (IFS), 2019)
We investigate the role of training in reducing the gender wage gap using the UK-BHPS which contains detailed records of training. Using policy changes over an 18 year period we identify the impact of training and work experience on wages, earnings and employment. Based on a lifecycle model and using reforms as a source of exogenous variation we evaluate the role of formal training and experience in de ning the evolution of wages and employment careers, conditional on education. Training is potentially important in compensating for the effects of children, especially for women who left education after completing high school.
Keywords: 330